4DCT Simulation With Synchronized Contrast Injection in Liver SBRT Patients. (February 2016) - Helou, Joelle; Karotki, Aliaksandr; Milot, Laurent; Chu, William; Erler, Darby; Chung, Hans T.
Background/Purpose: Delivering stereotactic body radiotherapy for liver metastases remains a challenge because of respiratory motion and poor visibility without intravenous contrast. The purpose of this article is to describe a novel and simple computed tomography (CT) simulation process of integrating timed intravenous contrast that could overcome the uncertainty of target delineation. Methods and Results: The simulation involves two 4-dimensional CT (4DCT) scans. The first scan only encompasses the immediate region of the tumor and surrounding tissue, which reduces the 4DCT scan time so that it can be optimally timed with intravenous contrast injection. The second 4DCT scan covers a larger volume and is used as the primary CT data set for dose calculation, as well as patient setup verification on the treatment unit. The combination of the two 4DCT scans allows us to optimally visualize liver metastases over all phases of the breathing cycle while simultaneously acquiring a long enough 4DCT data set that is suitable for planning and patient setup verification. Conclusion: This simulation technique allows for a better target definition when treating liver metastases, without being invasive.